The Religious Reflections of Martin Luther King Jr. on Justice and Equality - Latief, Hilman (UIN Sunan Kalijaga Yogyakarta, 2003)
Black churches and religion have played a unique role among black Americans, a role that was not necessarily so among white Americans. The historical background of black Americans, and the crucial fact of slavery, resulted in black churches and religion having a significant place up to the present times. Black churches have been the central institution in the most black communities.